Annexin 1 inhibits remifentanil-induced hyperalgesia and NMDA receptor phosphorylation via regulating spinal CXCL12/CXCR4 in rats. (July 2019) - Li, Tang; Wang, Haiyun; Wang, Jinxin; Chen, Yimeng; Yang, Chenyi; Zhao, Mingshu; Wang, Guolin; Yang, Zhuo
Highlights: Up-regulation of spinal ANXA1, CXCL12 and NMDAR after remifentanil exposure. Intrathecal Anxa12-26 ameliorated remifentanil-induced hyperalgesia. Anxa12-26 treatment increases spinal ANXA1 level after remifentanil infusion. Anxa12-26 treatment decreases CXCL12/CXCR4 expression after remifentanil infusion. Inhibition of CXCL12/CXCR4 reduces remifentanil-induced hyperalgesia. Abstract: Chemokines related neuroinflammation and N-methyl-d -aspartate receptor (NMDAR) mediated nociceptive transmission are pivotal determinants in the pathogenesis of opioid-induced hyperalgesia (OIH), but little is known about specific mechanism and treatment. Chemokine CXCL12 with its receptor CXCR4 is implicated in different pathological pain, moreover, neurotoxicity of CXCL12 is associated with NMDAR activation. Recent studies recapitulate the anti-nociception of Annexin 1 (ANXA1) in inflammatory pain. This study examined whether ANXA1 prevented remifentanil-caused OIH through modulating CXCL12 and NMDAR pathway in rats. Acute exposure to remifentanil induced mechanical allodynia and thermal hyperalgesia, which was accompanied by the increase of spinal ANXA1 and CXCL12/CXCR4 expression. Central injection of Anxa12-26 attenuated behavioral OIH in a dose-dependent manner, facilitated ANXA1 production, and inhibited up-regulation of CXCL12/CXCR4 level and NR2B-containing NMDAR phosphorylation. Moreover, pretreatment with AMD3100 reduced hyperalgesia and NR2B-containing NMDAR phosphorylation. Also, exogenous CXCL12 elicited pain hypersensitivity and NMDAR activation in naïve rats, which was reversed by the supplemental delivery of Anxa12-26 . These current findings indicate the participation of spinal CXCL12/CXCR4 and NR2B-containing NMDAR pathway in anti-hyperalgesic action of ANXA1 in OIH.